Effect of repetitive biphasic muscle electrostimulation training on vertical jump performances in female volleyball players - Marqueste, T.; Messan, F.; Hug, F.; Laurin, J.; Dousset, E.; Grelot, L.; Decherchi, P. (International Journal of Sport & Health Science, 2010)
The aim of this study is to describe the effects of transcutaneous muscular electrical stimulation on vertical jump performance (jumping height). Electromyostimulation (30 min/day, 10 sessions during 4 weeks) was applied, using a symmetric and biphasic rectangular pulses, with ramp modulation of both pulse duration and stimulation frequency. Ten healthy young women received this electrical stimulation program of the two thigh muscles (Vastus Lateralis or Biceps Femoris) and five unstimulated women were in a control group. Effects of the functional electrical stimulation were evaluated before, during the stimulating protocol, then a 4-week follow-up was performed after the end of exercises and stimulations protocols. Two different vertical jumps were carried out (squat and counter movement jumps). Performances were increased in all electrostimulated groups from the first week. These gains were still observed 4 weeks after the end of the protocol when the Vastus Lateralis muscles were electrostimulated. These results suggest that chronic electrical stimulation induces durable changes on the motor unit recruitment and performance when appropriate muscles were stimulated, and stimulation of thigh muscles weakly involved in jump is followed by a temporarily increase in performance that decreases immediately after the end of electrostimulation, maybe due to placebo effect.